Understanding national culture and ethics in organizations : a study of Eastern and Central Europe - Warter, Iulian; Warter, Liviu (Emerald Publishing Limited, 2020)
Understanding National Culture and Ethics in Organisations: A Study of Eastern and Central Europe reveals some leading questions in business research, linking ethics and national culture, with a particular emphasis on Eastern European countries.